Exploring the Determinants of Advanced Big Data Analytics Adoption in Zimbabwe’s Telecom Sector: A TOE Framework Analysis - Ngwendere, Jethro Simbarashe; Mlitwa, Nhlanhla (Journal of Information System and Informatics, 2025)
The way in which organisations conduct business has been revolutionised by Big Data Analytics (BDA). Several organisations have experienced improved productivity and effectiveness from the insights resulting from BDA which in turn impacts economic development. The adoption and use of BDA in the Zimbabwean telecommunication industry was limited. The aim of the research was to identify the factors limiting the adoption and usage of BDA within the Zimbabwean telecommunications industry. The objective of the research was therefore to pinpoint impediments which would then inform recommendations to improve the adoption and use of BDA in the Zimbabwean telecommunications industry. The study adopted critical realism and the Technology Organisation Environment (TOE) framework to identify the causal forces limiting the adoption and use of BDA. The findings indicate that IT infrastructure, service quality, senior management support, skills and expertise, financing, government policy, and economic conditions are the primary factors affecting BDA adoption.